1990
DOI: 10.1128/aem.56.8.2522-2528.1990
|View full text |Cite
|
Sign up to set email alerts
|

Common amino acid domain among endopolygalacturonases of ascomycete fungi

Abstract: The endopolygalacturonase (EC 3.2.1.15) enzymes produced in vitro by three ascomycete fungi, Aspergillus niger, Sckerotinia scierotiorum, and Colletotrichum lindemuthianum were studied by using thin-layer isoelectric focusing and activity stain overlay techniques. The polygalacturonases from A. niger and S. sclerotiorum consisted of numerous isoforms, whereas the endopolygalacturonase from C. lindemuthianum consisted of a single protein species. The most abundant endopolygalacturonase isoform produced by each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This indicates that the exoPG is likely to be a single polypeptide protein, while the native exoPMG is composed of two identical subunits. The Mrs of these exoenzymes are higher than those of the endoPGs which are secreted by this fungus and which are in the range of 28,000 to 43,000 (18,24).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…This indicates that the exoPG is likely to be a single polypeptide protein, while the native exoPMG is composed of two identical subunits. The Mrs of these exoenzymes are higher than those of the endoPGs which are secreted by this fungus and which are in the range of 28,000 to 43,000 (18,24).…”
Section: Resultsmentioning
confidence: 69%
“…Decomposition of plant cell walls during tissue invasion and pathogenesis is a characteristic feature of numerous plant diseases caused by phytopathogenic fungi (9,18). These fungi are able to produce a large array of cell walldegrading enzymes, both in culture and in diseased plant tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At pH 7.5 the activity was completely undetectable and at 8.5 minimal. The reported polygalacturonase enzyme activity oi Aspergillus nidulans was also highest at or below pH 4 (DEAN and TIMBERLAKE 1989) and that of Aspergillus niger and Sclerotinia sclerotiorum at pH 4.2 (KEON and WAKSMAN 1990). BAILEY and PESSA (1990) found that the pH optimum of the A. niger polygalacturonase was between pH 4.5-5.0.…”
Section: Detection Of Polygalacturonic Acid Hydrolyzing Activity and mentioning
confidence: 99%
“…Also, a single deletion of two amino acids is observed with respect to the sequences of the three other fungal polygalacturonases (data not shown). Alignment of the N-terminal amino acid sequences of these polygalacturonases with those of the major polygalacturonases of Colletotrichum lindeniuthiunum and Sclerotiniu sclerotiorunz [30] is shown in Fig. 5.…”
Section: Similarity Of Fungal Polygalacturonasesmentioning
confidence: 99%